Sistem Informasi Pengolahan Data Cuti dan Penerimaan Calon Karyawan Berbasis Website - Arif Budiman; Taqrim Ibadi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Information systems are an important part of the business world, because they can provide information about a company and carry out all kinds of activities. The purpose of this research is to build a website-based information system for processing leave data and hiring prospective employees at PT Lematang Coal Lestari, which previously did not have an information system to convey information about companies and job vacancies. Leave data processing still uses a written form, and the remaining leave is recorded using Microsoft Excel, so it is possible to cause input errors. Then the selection process for hiring new employees is carried out directly at the company's location, so it will take a lot of time. The methodology used is a qualitative research method with data collection techniques, namely observation and interviews, then the system development method used is the waterfall method. Data collection is the first stage, then followed by carrying out the following stages, namely design, program code generation, testing and support. The result of this research is the creation of a website-based information system for processing leave data and hiring prospective employees at PT Lematang Coal Lestari which can provide information about companies, products and job vacancies. The system created can help the HRD division process employee leave data easily and store it properly. This system can also facilitate decision making, thus helping companies in the process of hiring prospective employees. Keywords— Employee, Information System, Paid leave, Waterfall Method, Website.